Functional Characterizations Of Group II Chaperonin And Prefoldin From Hyperthermophilic Thermococcus Sp. KS-1 In Organic Co-Solvent - MUHAMAD SAHLAN; APRILIANA CAHYA KHAYRANI; NENG RISMA LIASARI (International Journal of Pharma and Bio Sciences, 2011)
Molecular chaperones have function in maintaining the quality of protein within a cell. Chaperones are indicating that are designed to function under stress. Chaperones functions under thermal stress have been intensively studied. Unfortunately, study about chaperone function under other stresses such as at extreme pressure or in chemical/solvent denaturants were limited. In this study we characterized the function of two kind chaperones from hyperthermophilic archaea Thermococcus sp. strain KS-1, prefoldin and chaperonin in organic co-solvent, by using polar protics and aprotic co-solvents. The results showed that the prefoldin and chaperonin only reduced aggregation of citrate synthase in 30% v/v acetonitrile which is polar aprotic. The chaperonin also showed ATPase activity in the 20% v/v acetonitrile. Based on those results we suggest that they could apply for maintaining protein substrate in the polar aprotic co-solvent for advance industrial application.